Precise Information on Primary Angle Closure Glaucoma - Chowdhury, Partha Haradhan; Shah, Brina Haren; Tiwari, Nripesh (International Journal For Research In Health Sciences And Nursing, 2020)
This paper describes about Primary Angle Closure Glaucoma, its Clinical Features and its Treatment modalities.